MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 016 BERINGIN JAYA KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Sutini Sutini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The background of this research is the low learning outcomes of science at the fourth grade students of SDN 016Beringin Jaya. The purpose of this study is to improve the learning outcomes of grade IV science through theadoption of cooperative learning model type make a match. This research is a classroom action researchconducted at SDN 016 Beringin Jaya, the subject of this research is the fourth grade students with 25 students.The results showed that after applying the cooperative learning model, make a match type can improve studentlearning outcomes. Seen in the acquisition of teacher activity data in the first cycle of the 1st meeting with apercentage of 56%, the second meeting with a percentage of 69.5%, in the second cycle at the third meeting thepercentage was 83%, and at the 4th meeting the percentage obtained 95%. Data on student activity in the firstcycle of the 1st meeting was 55.5%, the second meeting was 66.5%, in the second cycle the third meeting was80%, and the fourth meeting was 93%. Data on the improvement of learning outcomes in the initial dataobtained an average of 68.5, in daily I repetitions at 78, and on daily tests II at 87.MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCHUNTUK MENINGKATKAN HASIL BELAJAR IPASISWA KELAS IV SDN 016 BERINGIN JAYA KECAMATAN SINGINGI HILIRKABUPATEN KUANTAN SINGINGI